Políticas públicas, agricultura familiar e desenvolvimento rural no Norte do Tocantins: Um estudo sobre o intercâmbrio mercantil na cidade de Araguaína - Feitosa, Claudio Almeida (Univsersidade Federal do Tocantins, 2023)
The issue of rural development in Brazil has always been a major challenge, especially for family farming. In a way, the agricultural scenario has always favored large estates to the detriment of family farming. In this sense, this work sought to deepen the discussion on rural development, which is so relevant when it comes to combating rural poverty, hunger and unemployment. In order to do so, it was discussed how slow rural development took place in Brazil and how the creation of public policies aimed at family farming can contribute to human emancipation and to face food and nutritional insecurity, which have reached large masses in Brazil and in the world. . Old public policies, such as the National School Feeding Program, reformulated to serve family farming and combat food insecurity in schools, as well as the Food Acquisition Program, which emerged in a scenario of protagonism for family farming, were also addressed. in this research. It was also observed, in the open market, a traditional instrument of family agriculture that is still considered the main market for the flow of family agricultural production. Finally, the implementation and strengthening of public policies aimed at rural development for the insertion of family farmers can bring satisfactory results in rural and urban environments. In this sense, it is relevant to maintain and expand public policies that aim to guarantee the inclusion of family farmers in the mercantile exchange, necessary actions in the fight against unemployment and food insecurity. The open market, which is also part of the lower circuit of the urban economy, presents itself as a democratic channel for family farming to sell what it produces, therefore, this research portrays the difficulties experienced by farmers in participating in the mercantile exchange, be it institutional or in spaces public such as fairs.